Synergistic enhancing effect for mechanical and electrical properties of tungsten copper composites using spark plasma infiltrating sintering of copper-coated graphene - Wenge Chen (Nature Portfolio, 2017)
Abstract Successful applications of WCu alloys in high voltage electrical switches require their high strength and excellent conductivity. Unfortunately, the strategies for increasing their strength such as doping with fine particles and alloying often significantly decrease their conductivity. In this paper, we developed a new pathway for fabricating WCu alloys using spark plasma infiltrating sintering of copper-coated graphene (Cu@Gr) composite powders. Cu@Gr was found to partially prevent the formation of WC after sintering, and graphene was uniformly distributed on the surfaces of network Cu phases. Electrical conductivity of 38.512 M·S/m, thermal conductivity of 264 W·m−1·K−1 and microhardness of 278 HV were achieved for the sintered WCu composites doped with only 0.8 wt.% Cu@Gr powders, which showed 95.3%, 24.3%, 28% enhancement compared with those from the conventional sintering using the undoped WCu powders.